Lola Montez (1818–1861) - Stieler, Joseph Karl, 1781-1858 (artist):::Creator::: (2020)
Reproduction of an oil portrait of Lola Montez by Joseph Stieler from 1847, from the original at the Schloß Nymphenburg, Munich